2023
DOI: 10.21203/rs.3.rs-2573180/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between HIV serostatus and premalignant cervical lesions among women attending a cervical cancer screening clinic at a tertiary care facility in southwestern Uganda: a comparative cross-sectional study

Abstract: Background: Uganda has approximately 1.2 million people aged 15–64 years living with human immunodeficiency virus (HIV). Previous studies have shown a higher prevalence of premalignant cervical lesions among HIV-positive women than among HIV-negative women. Additionally, HIV-infected womenare more likely to have their human papilloma virus (HPV) infection progress to cancer than non-HIV-infected women. We determined the prevalence of premalignant cervical lesions and their association with HIV infection among … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For instance, studies conducted in Ruanda and Ethiopia revealed that HIV-infected women have a higher risk of precancerous cervical lesion. 14,15 Conversely, these reports are argued by the findings of other researchers. 16,17 Besides to the variability in the presence of a significant association between HIV infection and precancerous cervical lesion, the strengths of the reported measures of association are also different across studies that report significant associations.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…For instance, studies conducted in Ruanda and Ethiopia revealed that HIV-infected women have a higher risk of precancerous cervical lesion. 14,15 Conversely, these reports are argued by the findings of other researchers. 16,17 Besides to the variability in the presence of a significant association between HIV infection and precancerous cervical lesion, the strengths of the reported measures of association are also different across studies that report significant associations.…”
mentioning
confidence: 85%
“…However, the findings are not consistent throughout the studies. For instance, studies conducted in Ruanda and Ethiopia revealed that HIV‐infected women have a higher risk of precancerous cervical lesion 14,15 . Conversely, these reports are argued by the findings of other researchers 16,17 …”
Section: Introductionmentioning
confidence: 98%